Penelitian Pendahuluan tentang Dampak Penerapan Model Pembelajaran Couple Card Teams Tournament (CCTT) terhadap Aktivitas Belajar dan Hasil Belajar Biologi Siswa Kelas X SMA - Rahmat Hidayat (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret, 2018)
The objective of this study is to describe the impact of the application of CCTT learning model on learning activities and biology learning outcomes of students Class X IPA 2 SMA Negeri 1 Merlung. This study was descriptive research, the subjects were the 25 of class X IPA 2 school year 2017/2018. Research data were collected through observation, documentation and test. The Data were analyzed qualitatively through reduction and display of data, and make conclusions. The results showed that the application of CCTT learning model has a good impact on learning activities and biology learning outcomes. High learning activities have been seen from the achievement of indicators of 89,8%, with average of 22,4 students have been involved in every aspect of learning activities. Percentage of mastery of learning outcomes amounted 84% (21 students), the average learning outcomes was 73,3 with the highest score was 90 and the lowest score was 50. The results confirmed that CCTT learning